2020
DOI: 10.3390/biom11010010
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin as a Natural Therapeutic Candidate for the Treatment of Influenza Virus

Abstract: The medical burden caused by respiratory manifestations of influenza virus (IV) outbreak as an infectious respiratory disease is so great that governments in both developed and developing countries have allocated significant national budget toward the development of strategies for prevention, control, and treatment of this infection, which is seemingly common and treatable, but can be deadly. Frequent mutations in its genome structure often result in resistance to standard medications. Thus, new generations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 150 publications
(193 reference statements)
1
42
0
1
Order By: Relevance
“…Our findings indicated that the formation of peptide bonds was effective to screen more flavonoids to intervene COVID-19. Quercetin and other flavonols are common nutraceuticals with antiviral activities, such as influenza virus, hepatitis B virus, Zika virus, and Ebola viruses (Mehrbod et al 2021; Parvez et al 2020; Wong et al 2017; Qiu et al 2016). In this study, we took advantage of our recent strategy to perform this docking simulation of flavonols and dihydroflavonols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings indicated that the formation of peptide bonds was effective to screen more flavonoids to intervene COVID-19. Quercetin and other flavonols are common nutraceuticals with antiviral activities, such as influenza virus, hepatitis B virus, Zika virus, and Ebola viruses (Mehrbod et al 2021; Parvez et al 2020; Wong et al 2017; Qiu et al 2016). In this study, we took advantage of our recent strategy to perform this docking simulation of flavonols and dihydroflavonols.…”
Section: Discussionmentioning
confidence: 99%
“…In general, flavonols and dihydroflavonols are strong antioxidants with multiple benefits to human health (Moon et al 2001; Murota and Terao 2003; Egert et al 2008; Chopra et al 2000; Hertog et al 1993b; de Vries et al 1998; Kolhir et al 1996; Teselkin et al 1998; Teselkin et al 2000; Weidmann 2012). Furthermore, studies have reported that quercetin and its derivatives have antiviral activity (Mehrbod et al 2021; dos Santos et al 2014; Cheng et al 2015). Based on these previous findings, we hypothesized that flavonols and dihydroflavonols might inhibit the M pro activity of SARS-CoV-2 and HCoV-229E.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of studies reported the potent ability of quercetin as protease inhibitor when used against virus infection: Bachmetov et al demonstrated a direct inhibitory effect of quercetin on HCV NS3 serine protease catalytic activity, while Yao et al showed that quercetin potently inhibited Enterovirus 71 (EV71) 3C-protease activity, blocking EV71 replication [ 63 , 64 ]. The same anti-replication activity has been investigated in computational studies on Middle East respiratory syndrome-coronavirus (MERS-CoV) and SARS-CoV, where results proved a strong interaction between quercetin and the catalytic site of viral 3C-like protease [ 65 , 66 , 67 ]. It has also been reported that co-administration of quercetin, as a promising inhibitor of crucial viral enzymes (reverse transcriptase, integrase and protease), and Vitamin C could be suggested for prophylaxis in a high-risk population and for the treatment of COVID-19 patients as support therapy: the synergistic antiviral action could be due to the overlap of multiple properties of the different compounds, such as antioxidant and immunomodulatory properties, and to the capability of ascorbate to recycle quercetin, increasing its efficacy [ 68 ].…”
Section: Quercetinmentioning
confidence: 93%
“…Quercetin and its derivatives: Quercetin, like other flavonoids, is a polyphenolic compound, the main structural element of which is composed of two aromatic rings, A and B, connected by a three-carbon bridge, forming a pyran or pyrone (in the presence of double bonds) ring [103]. This group of compounds has long attracted attention as potential therapeutic agents for the fight against respiratory tract infections [104].…”
Section: In Vivo Efficacy Of Polyphenolic Compoundsmentioning
confidence: 99%